Penguatan Literasi dan Manajemen Keuangan Guna Mendukung Keberlanjutan Organisasi Sanggar Tari Tradisi Kalijaro Taruno Mudo - Yeni Indraningtyas; Pipit Sundari; Teguh Harso Widagdo; Satria Avianda Nurcahyo; Ahmad Ali (Jurnal Kabar Masyarakat, 2026)
The sustainability of traditional arts organisations depends not only on cultural preservation, but also on sound financial management. The Kalijaro Taruno Mudo Traditional Dance Troupe in Karang Jati Village still faces challenges in the areas of financial literacy and management, namely the continued use of manual bookkeeping methods and a lack of financial governance. This community service initiative aims to strengthen financial literacy and management to support the sustainability of the dance troupe. The method employed is the Community Empowerment approach, which involves community-based empowerment through the stages of preparation, implementation, evaluation and follow-up. Activities included training in financial literacy, guidance on simple bookkeeping, budget preparation and financial reporting. The results of the activities demonstrated an improvement in the committee members’ understanding and skills in recording financial transactions, drawing up budgets, and presenting financial reports in a more accountable manner. Furthermore, the development of a work plan and a mechanism for periodic evaluation has contributed to better organisational governance. This programme demonstrates that strengthening financial literacy and management can support the sustainability of community-based arts and culture organisations.